Digital Transformation and Citizen Trust in Local Government Services: Evidence from a District-Level Study in Indonesia - Dwiyanti, Andi Amitya Resty; Marhati, Marhati (PUBLICUS: Jurnal Administrasi Publik, 2026)
Digital transformation has become a central reform agenda in public administration, particularly in improving the quality and credibility of local government services. In decentralized governance systems, citizen trust is a crucial outcome that determines the effectiveness and sustainability of digital governance initiatives. This study examines the effect of digital transformation on citizen trust in local government services in Awangpone District, Bone Regency, Indonesia. Using a quantitative approach, data were collected through a structured survey administered to 412 residents who had accessed local government services within the previous twelve months. Digital transformation was operationalized as a multidimensional construct encompassing service availability, ease of use, system reliability, responsiveness, and perceived efficiency, while citizen trust was measured through indicators of institutional competence, transparency, procedural fairness, integrity, and overall confidence. Statistical analysis was conducted using descriptive statistics, correlation analysis, and multiple linear regression. The findings indicate that digital transformation has a significant positive effect on citizen trust in local government services. The results suggest that the quality of digital service implementation plays a critical role in shaping institutional trust at the district level. This study contributes to the public administration and digital governance literature by providing district-level empirical evidence from a developing-country context, addressing the limited focus of previous studies on metropolitan or national settings. The findings offer practical implications for local governments seeking to strengthen citizen trust through inclusive and effective digital transformation strategies.